Shareholders' authority to reorganize representation powers in a joint-stock company Regarding the comment on (Charter Law 730/66Q) - Akram Amr Yaqoub Moussa (Journal of Libyan Academy Bani Walid, 2025)
Legal representation of a company is one of the most prominent issues in commercial law. It relates to the legal capacity of those who initiate litigation on behalf of the company. This capacity determines the validity of legal actions taken in its name before third parties and their binding force toward parties dealing with it. The importance of this issue lies in the fact that any error or ambiguity in determining who has the capacity to represent the company may result in the invalidity of the action and its lack of legal effect. This comment comes on the occasion of the Supreme Court's reversal in (C.M. 301/66Q) of (C.M. 730/64Q) regarding the extent to which the general manager is authorized to represent the company. This raises a legal question regarding the validity of both rulings, and which one is based on sound legal principles.